1989
DOI: 10.1002/cne.902800105
|View full text |Cite
|
Sign up to set email alerts
|

Dopamine‐like immunoreactivity in the brain and suboesophageal ganglion of the honeybee

Abstract: The distribution of dopamine in the brain and suboesophageal ganglion of the honeybee Apis mellifera was investigated by means of immunocytochemistry with a well-characterized antiserum against dopamine. The binding of the antiserum in paraffin serial sections was studied with the peroxidase-antiperoxidase method. Dopamine-like immunoreactive neurons are present in most parts of the brain and in the suboesophageal ganglion. Only the optic lobes are devoid of label. There are ca. 330 dopamine immunoreactive som… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
123
3

Year Published

1996
1996
2013
2013

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 128 publications
(142 citation statements)
references
References 39 publications
16
123
3
Order By: Relevance
“…We chose to examine dopamine-evoked responses in mushroom body calyces because these structures can be easily isolated from the brain. Moreover, intrinsic mushroom body neurons (Kenyon cells) express all three of the dopamine receptor genes identified in honey bees, Amdop1, Amdop2, and Amdop3 (25,26,29,30), and mushroom bodies receive extensive input from dopamine-immunoreactive neurons (31).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We chose to examine dopamine-evoked responses in mushroom body calyces because these structures can be easily isolated from the brain. Moreover, intrinsic mushroom body neurons (Kenyon cells) express all three of the dopamine receptor genes identified in honey bees, Amdop1, Amdop2, and Amdop3 (25,26,29,30), and mushroom bodies receive extensive input from dopamine-immunoreactive neurons (31).…”
Section: Resultsmentioning
confidence: 99%
“…and A.R.M., unpublished data). Whether changes at the level of the mushroom bodies contribute to the QMP-induced changes in locomotor activity, however, remains unclear because many regions of the brain are densely innervated by dopaminergic neurons (31) and all are potential targets for modulation by QMP.…”
Section: Discussionmentioning
confidence: 99%
“…In Schäfer and Rehder's study, dopamine-like immunoreactive neurons were identified in most parts of the brain and in the suboesophageal ganglion (Schäfer and Rehder, 1989) (Fig.4). Only the optic lobes were devoid of staining.…”
Section: The Neural Basis Of Aversive Learning: Us Signalingmentioning
confidence: 86%
“…Similarly, agonists could be designed that couple the DopR99B receptor to one or another of the two second messenger pathways that it potentially can activate. Such compounds could lead to the development of highly effective insect control agents, given the preferential expression of this Drosophila dopamine receptor in mushroom bodies (Han et al, 1996) and the likely involvement of dopamine in the processes of learning and memory in the insect nervous system (Tempel et al, 1984;Budnik and White, 1988;Schafer and Rehder, 1989;Buchner, 1991;Nassel and Elekes, 1992). Further, genetic studies on dopamine receptor mutants in Drosophila could identify the physiological roles of the separate activation of each of the two second messenger systems potentially coupled to the DopR99B receptor, because a variation in the local G-protein environment of different cell types expressing this receptor might allow the receptor to be coupled differently in different cell types.…”
Section: Discussionmentioning
confidence: 99%